2000
DOI: 10.1093/humrep/15.11.2341
|View full text |Cite
|
Sign up to set email alerts
|

Day 3 serum inhibin B and FSH and age as predictors of assisted reproduction treatment outcome

Abstract: Recent reports investigating the value of basal inhibin B determination as a predictor of ovarian reserve and assisted reproduction treatment have led to discordant results. This study was undertaken to further assess the relative power of day 3 inhibin B and follicle stimulating hormone (FSH) (defined before treatment) and the woman's age both as single and combined predictors of ovarian response and pregnancy in an in-vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) programme. A total of 120… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
1
11

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(83 citation statements)
references
References 19 publications
5
66
1
11
Order By: Relevance
“…In a recent study, basal FSH level was reported to be significant and better predictor of cycle cancellation when compared with age and inhibin B, while age was better than both FSH and inhibin B levels in predicting pregnancy (27). Consequently, on the basis of our data and others, it may be suggested that basal inhibin B is not a better predictor of ovarian response than age and basal FSH (21,27). It should also be taken into consideration that there is no international assay standard for inhibin B yet, and comparison of different inhibin B values between various studies seems to be a problem.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In a recent study, basal FSH level was reported to be significant and better predictor of cycle cancellation when compared with age and inhibin B, while age was better than both FSH and inhibin B levels in predicting pregnancy (27). Consequently, on the basis of our data and others, it may be suggested that basal inhibin B is not a better predictor of ovarian response than age and basal FSH (21,27). It should also be taken into consideration that there is no international assay standard for inhibin B yet, and comparison of different inhibin B values between various studies seems to be a problem.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, it has been shown that age and the number of the oocytes retrieved were the strongest predictors of success; and only a combination of lower FSH (FSH <11.22 mIU/mL) and higher inhibin B (inhibin B ≥76.5 pg/mL) was associated with a greater chance for a successful outcome in IVF (21). In a recent study, basal FSH level was reported to be significant and better predictor of cycle cancellation when compared with age and inhibin B, while age was better than both FSH and inhibin B levels in predicting pregnancy (27). Consequently, on the basis of our data and others, it may be suggested that basal inhibin B is not a better predictor of ovarian response than age and basal FSH (21,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one report, the pregnancy rate after six cycles of ovulation induction was four times higher in patients Ͻ40 years of age than in patients 40 years of age or older, while both had elevated FSH levels (14). In IVF populations, a moderately elevated FSH level had limited predictive value in young women (9) and age seemed a more important predictive factor for the occurrence of pregnancy than FSH (8,18,25). In contrast, it has recently been shown that younger IVF patients with either a poor ovarian response in IVF or elevated FSH levels performed as poorly as the older patients, although pregnancy rates in the older women with raised FSH levels may have been overestimated because of selection (10).…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical markers identified are FSH, inhibin B, AMH, and estradiol. Biophysical markers include antral follicle count and ovarian volume [3]. Many researchers have used single as well as multiple markers to assess the ovarian reserve.…”
Section: Introductionmentioning
confidence: 99%